A theory-based explicit calculation model for variable speed scroll compressors with vapor injection. (April 2018) - Sun, Haoran; Hu, Haitao; Wu, Jingwei; Ding, Guoliang; Li, Geping; Wu, Chengyun; Wang, Xuyang; Lv, Zhongyuan
Highlights: A theory-based explicit model of the compressor with vapor injection was developed. Explicit equations of suction and injection mass flow rates were established. Explicit equations of total input power and discharge temperature were developed. The accuracy and calculation speed of the proposed model were verified. Abstract: For accurately and quickly predicting the performance of variable speed scroll compressors with vapor injection, a theory-based explicit calculation model should be developed. In the present study, the model of the compressor with vapor injection was proposed by developing the theory-based explicit equations for the compressor performance parameters. In the model, the suction mass flow rate was expressed as the function of normalized volumetric efficiency, and the injection mass flow rate was computed by partial linearization method; the total input power was linearized by the second-order Taylor expansion; the equation of discharge temperature was developed using the heat leakage factor to realize the explicit calculation by avoiding the iterative solution of thermal loss through the compressor shell. The model verification results show that, the proposed model has a good prediction accuracy, and the calculation speed of the present model is 10 2 –10 3 times faster than that of the existing models.